Crossing ocean parkway readings by an Italian American daughter - Torgovnick, Marianna 1949- (Univ. of Chicago Press, 1994)
Growing up as an Italian American in Bensonhurst, Marianna De Marco longed for college, culture, and upward mobility. Her daydreams circled around WASP heroes on television - like Robin Hood and the Cartwright family - but in Brooklyn she never encountered any. So she associated moving up with Ocean Parkway, a street that divides the working-class Italian neighborhood where she was born from the middle-class Jewish neighborhood into which she married